2023
DOI: 10.1177/17562864231180717
|View full text |Cite
|
Sign up to set email alerts
|

Acute reperfusion treatment and secondary prevention of cancer-related stroke: comprehensive overview and proposal of clinical algorithm

Abstract: Cancer-related stroke (CRS), referring to ischemic stroke occurring in cancer patients without other clear etiology, represents a clinical challenge, as it is associated with unfavorable clinical outcomes including high rates of recurrence and mortality. There are scarce international recommendations and limited consensus statements on CRS management. For this comprehensive overview, the available studies/reviews/meta-analyses on the use of acute reperfusion and secondary prevention treatments for cancer patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…Patients with cancer are at elevated risk of recurrent stroke due to cancer-associated coagulation disorder. 23) Three of the seven patients in our series experienced major ischemic stroke recurrence with high D-dimer levels during hospitalization. Two of these patients could not be treated with anticoagulant therapy because of a substantial risk of cancer-related bleeding.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Patients with cancer are at elevated risk of recurrent stroke due to cancer-associated coagulation disorder. 23) Three of the seven patients in our series experienced major ischemic stroke recurrence with high D-dimer levels during hospitalization. Two of these patients could not be treated with anticoagulant therapy because of a substantial risk of cancer-related bleeding.…”
Section: Discussionmentioning
confidence: 79%
“…Several studies have reported on acute recanalization therapies, including mechanical thrombectomy, for cancerassociated ischemic stroke overseas. [23][24][25] Intravenous tissue plasminogen activator thrombolysis is often not indicated due to hematological problems and recent surgery of cancer. 2,26) Instead, a mechanical thrombectomy was performed.…”
Section: Discussionmentioning
confidence: 99%
“…Studies analysing MT outcomes in CP either assess all patients with active cancer or a subgroup of patients with cancer-related stroke (CRS). CRS is defined as a cryptogenic stroke (with no evidence of conventional stroke mechanisms) in a patient with malignancy, with features of hypercoagulation (elevated D-dimer level or VT) and/or infarctions present in multiple vascular territories [ 15 ]. Studies evaluating outcomes of MT in patients with CRS (defined as such) found that they presented with higher mortality and worse functional outcome in long-term observation, both compared to patients without cancer [ 16 , 17 ], and patients with cancer and stroke due to a different aetiology [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 21 , 22 , 24 Consequently, a recent comprehensive review on cancer-related stroke emphasized the need to collect further data on these patients. 25 Given the importance of EVT in addition to IVT in case of large vessel occlusion (LVO), 26 , 27 we sought to evaluate the outcome and rate of bleeding complications after IVT and/or EVT in a large cohort of AIS patients with active malignancy, history of cancer or without cancer.…”
Section: Introductionmentioning
confidence: 99%